Figure 1 from: Chiapella JO, Xue Z-Q, Greimler J (2021) The genus Deschampsia and the epithet " alpina". PhytoKeys 181: 95-103. https://doi.org/10.3897/phytokeys.181.69546 - Chiapella, Jorge O.; Xue, Zhi-Qing; Greimler, Josef (Zenodo, 2021)
Figure 1 Comparison of selected morphological traits in Deschampsia cespitosa s.l. in North America (left panel) and North Central Europe (right panel): plant height A panicle length B panicle width C ligule length D lower glume length E lemma length F awn length G taxa codes: Deschampsia cespitosa subsp. septentrionalis (s); D. cespitosa subsp. orientalis (o); D. cespitosa subsp. glauca (g); D. cespitosa subsp. neoalpina (n); D. cespitosa subsp. cespitosa (c); D. cespitosa ssp. mackenzieana (m); D. cespitosa ssp. beringensis (b); D. cespitosa ssp. littoralis (l); D. cespitosa subsp. wibeliana (w); D. cespitosa subsp. parviflora (p). Redrawn from Chiapella (2000) and Chiapella et al. (2011). All in mm.